OFFICE ADMINISTRATION MANAGEMENT THROUGH MODERN ARCHIVES MANAGEMENT TRAINING IN IMPROVING PUBLIC SERVICES - Tri Anggraini; Anita Lassa; Handrianus V.M. Wula (Abdimas Galuh, 2022)
This service is motivated by the needs and problems of partners. The results of initial observations made by the service team, the service team found various partner problems related to the management of Archives in Naiola Village, TTU District, including the following: First, Lack of knowledge and skills of village officials related to archives; Second, lack of facilities and infrastructure to store existing archival documents; Third, there is no part of the Village Apparatus that specifically takes care of the management of Archives; Fourth, partners only carry out conventional archive management. In fact, the Village Government is asked to be able to document all Village activities both in conventional form or in electronic form because basically archive management that only relies on conventional types is not reliable because it is not effective and efficient enough. Therefore, efforts are needed to improve the skills of village officials and equip village officials with additional knowledge and skills of village administration management through modern archive management training to improve public services. This service activity is carried out according to the predetermined plan. This service activity received a lot of support, especially from the village head of Naiola Kab.TTU who also thought that this activity provided motivation and a more modern picture for village officials related to technological advances that must be utilized properly by village officials as an effort to improve public services.